2021
DOI: 10.1111/vox.13190
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion requirements and alloimmunization to red blood cell antigens in orthotopic liver transplantation

Abstract: Background and Objectives Orthotopic liver transplantation (OLT) has been associated with high blood transfusion requirements. We evaluated the transfusion needs and frequency of alloimmunization to RBC antigens among OLT recipients pre‐ and post‐transplantation. Materials and Methods We reviewed the medical records of patients who underwent a first OLT between January 2007 and June 2017. Transfusions given only during the perioperative period, defined by 1 week before OLT until 2 weeks following OLT, were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…OLT has developed throughout the years and become the standard of care for advanced liver disease. Although the use of blood components during OLT has considerably decreased over the past two decades, transfusion demands are still significant, especially during the perioperative period [2]. There is also wide variation in transfusion rates between transplantation centres, which can be attributed to specific patient population, surgical techniques, differences in institutional transfusion practices, variable use of antifibrinolytics and intraoperative blood salvage, among other variables [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OLT has developed throughout the years and become the standard of care for advanced liver disease. Although the use of blood components during OLT has considerably decreased over the past two decades, transfusion demands are still significant, especially during the perioperative period [2]. There is also wide variation in transfusion rates between transplantation centres, which can be attributed to specific patient population, surgical techniques, differences in institutional transfusion practices, variable use of antifibrinolytics and intraoperative blood salvage, among other variables [11].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we reviewed the medical records of OLT patients to during the perioperative period [2]. There is also wide variation in transfusion rates between transplantation centres, which can be attributed to specific patient population, surgical techniques, differences in institutional transfusion practices, variable use of antifibrinolytics and intraoperative blood salvage, among other variables [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that 4%–23% of liver transplant patients can have red cell alloantibodies pre‐transplant [3]. Unfortunately, most hospitals do not have access to even a local or regional registry of RBC antibodies to look up patients' previous history.…”
Section: Discussionmentioning
confidence: 99%